Fostering Creative Thinking in a Digital World - Newton, Douglas P.; Newton, Lynn D. (International Journal for Talent Development and Creativity, 2020)
We are now moving rapidly into a new world, one shaped by the Fourth ‘Industrial’ Revolution. This world is one in which digital technologies in various forms will shape work, play and everyday life. Such technologies, unlike the relatively passive ones of the past, are adaptive, able to learn and make decisions and changes using their artificial intelligence (AI). AI, however, has its limits, and productive thought continues to need fostering in the classroom. As a consequence, education systems around the world must respond in what has been called the Fourth Education Revolution. This article explores the potential relationship between AI, creative thinking and education, and the fostering and development of human creative thinking supported by AI. Some significant omissions in current notions of AI support for creative thinking are presented, and some cautionary thoughts offered. The article concludes with recommendations for a more structured and comprehensive provision of AI support.